Protective role of intraperitoneally administered vitamins C and E and selenium on the levels of lipid peroxidation in the lens of rats made diabetic with streptozotocin - Naziroglu, M; Dilsiz, N; Çay, M (Humana Press Inc, 1999)
The aim of this work was to determine the protective effects of intraperitoneally administered vitamins C and E and selenium on the lipid peroxidation (MDA), glutathione peroxidase (GSH-Px), reduced glutathione (rGSH) activities in the lens of rats induced diabetic with streptozotocin (STZ). Lenses in the diabetic control group had a slightly higher mean level of MDA compared with lenses of the vitamin E and selenium groups, although the mean levels of MDA were significantly lower in control, combination, and vitamin C groups than in the diabetic control group (p < 0.05 and p < 0.01). However, MDA levels were significantly lower in vitamin C, vitamin E, and combination groups than in controls (p < 0.01). The GSH-Px activities of lenses were significantly higher in vitamin C-, vitamin E- and selenium-injected groups than that in the diabetic control group (p < 0.01), whereas, the activity of GSH-Px was significantly lower in the diabetic control group than in the control group. Ln addition, the rGSH content was seen to decrease only in the vitamin C group compared to both control and diabetic control groups (p < 0.05). In conclusion, the results from these experiments indicate that vitamins C and E and selenium can protect the lens against oxidative damage, but the effect of vitamin C appears to be much greater than that of vitamin E and selenium.
Keywords: selenium; vitamin C; vitamin E; diabetic; lens